Magnetic properties of the warwickite MnMgBO4. (March 2019) - Eremina, R.M.; Moshkina, E.M.; Muftakhutdinov, A.R.; Gilmutdinov, I.F.; Lyadov, N.M.
Abstract: Magnetic properties of a new single crystal MnMgBO4 have been studied. It was determined that below 16 K antiferromagnet spin order was observed with the axis of easy magnetization along the c axis crystal. The short antiferromagnetic range order was observed below 100 K. The Curie–Weiss temperature has been determined in single crystal MnMgBO4 as θ CW  = −98 K and the frustration parameter has been estimated as 6.125. Highlights: Magnetic properties of MnMgBO4 have been studied with antiferromagnet spin order at 16 K. The short antiferromagnetic range order was observed below 100 K in new crystal MnMgBO4 . The lambda point has been observed in the temperature dependence of the molar heat capacity at 16K.